BLUE BOND FINANCING MODEL FOR ENVIRONMENTAL SOCIAL GOVERNANCE SEAWEED FARMING - Dhoya Safira Tresna Lestari; Prima Naomi (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2025)
This study investigates the potential of Blue Bonds, grounded in Environmental, Social, and Governance (ESG) principles, as a financing mechanism to advance sustainable seaweed farming and empower coastal communities in Indonesia. Employing a mixed-methods approach, the research examines the interplay between ESG adoption, adherence to Blue Bond guidelines, project feasibility, and local socio-economic outcomes. Quantitative analysis of survey data from 250 respondents using PLS-SEM is complemented by qualitative evidence from stakeholder interviews and field observations. Findings indicate that robust ESG practices foster greater compliance with guidelines, improve project viability, and enhance competitiveness. Nevertheless, the expansion of ESG initiatives is hindered by challenges such as scarce affordable financing, limited institutional capacity, and ambiguous regulatory frameworks. Key obstacles identified include restricted credit access and governance weaknesses, while opportunities exist through ESG certification and emerging market incentives. The study concludes that Blue Bonds hold substantial promise for integrating sustainability objectives with inclusive economic development, offering a pathway for resilient growth among Indonesia’s coastal communities.